The History in DNA: A Proposal to Generate a Change of Vision of Science in School - Cortez, Leonardo A. (2016)
Currently, in science teaching and in particular, natural science teaching there are concepts in the school that have a high level of abstraction. Concepts, such as atom, gene, mole and energy, among others are difficult to explain in an understanding manner to students. This situation requires the teacher to design alternative strategies to promote meaningful learning. Give priority to teaching concepts in science promotes the conception of science as a finished, infallible construct outside the context and does not evolve; turning science learning into something monotonous and uninteresting for students. According to some researches in the line of history and epistemology of sciences, its importance and advantages are recognized to promote not only a conceptual and formal education, but also to broaden the spectrum of possibilities that allow the students to transform conceptions of science into a more dynamic and participatory paradigm. Recognizing the benefits of the use of history in science teaching, a proposal is made for the DNA structure teaching in secondary school students within the framework of the Master in Teaching of Sciences of the Fundación Universidad Autónoma de Colombia, under this perspective.